2019
DOI: 10.1016/j.ijppaw.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of red panda as an intermediate host of Toxoplasma gondii and Sarcocystis species

Abstract: Toxoplasma gondii has been found to infect almost all warm-blooded animals; however, some hosts lack direct evidence of T. gondii infection. The red panda ( Ailurus fulgens ) is an endangered species that mainly lives in temperate forests of South Asia. Here, T. gondii infection in red pandas from zoos in China were reported. Antibodies to T. gondii were found in 14.3% (2/14) of red pandas via the modified ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The genotype of TgTigerCHn4 was ToxoDB#2, and 3/3 for the ROP18/ROP5 combination, indicating avirulence for mice. The genotype of ToxoDB#20 has been reported in cats, dogs, sand cats, red pandas, and serval from Africa and Asia ( Dong et al, 2019 ; Dubey et al, 2007 , 2010 , 2013 ; El Behairy et al, 2013 ; Al-Kappany et al, 2010 ; Tian et al, 2014 ; Yang et al, 2019b ). ToxoDB#20 T. gondii strains have been found in red pandas and serval from central China, both were 3/4 for the ROP18/ROP5 combination, avirulence for mice and low rate of brain cyst formation ( Dong et al, 2019 ; Yang et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of TgTigerCHn4 was ToxoDB#2, and 3/3 for the ROP18/ROP5 combination, indicating avirulence for mice. The genotype of ToxoDB#20 has been reported in cats, dogs, sand cats, red pandas, and serval from Africa and Asia ( Dong et al, 2019 ; Dubey et al, 2007 , 2010 , 2013 ; El Behairy et al, 2013 ; Al-Kappany et al, 2010 ; Tian et al, 2014 ; Yang et al, 2019b ). ToxoDB#20 T. gondii strains have been found in red pandas and serval from central China, both were 3/4 for the ROP18/ROP5 combination, avirulence for mice and low rate of brain cyst formation ( Dong et al, 2019 ; Yang et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the geographic distribution of ToxoDB#20 is summarized in Figure . ToxoDB#20 isolates have been isolated from cats (Al‐Kappany et al, ; Dubey et al, ; Tian et al, ), dogs (Behairy et al, ; Dubey et al, ), sand cats (Dubey et al, ) and red pandas (Yang et al, ). Comparison of genotypes indicated that ToxoDB#20 differs from Chinese 1 (ToxoDB#9) at locus PK1, but they probably belong to the same ancestral clade with Type II lineage.…”
Section: Discussionmentioning
confidence: 99%
“…The virulent phenotype was supported by infection in mice (low cyst formation rate and avirulence) (Table ). The other ToxoDB#20 strain isolated from a red panda ( Ailurus fulgens ) was also avirulent in mice, and it also had the same ROP18 / ROP5 genotype as TgServalCHn1 (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/genes14081606/s1, Table S1: Summary of viable T. gondii isolates (n = 169) from animals and humans in China [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Summary of viable T. gondii isolates (n = 169) from animals and humans in China [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
mentioning
confidence: 99%